The immune response of rhesus macaques to novel vaccines comprising hepatitis B virus S, PreS1, and Core antigens. Issue 26 (18th June 2018) - Chuai, Xia; Xie, Bangxiang; Chen, Hong; Tan, Xinyi; Wang, Wen; Huang, Baoying; Deng, Yao; Li, Wenhui; Tan, Wenjie
Highlights: We developed novel DNA and viral vector based vaccines comprising the S, PreS1, and Core antigens of HBV. This study first explored the immune responses of rhesus macaques to novel vaccines in a longitudinal study up to 98 weeks. The immunity against S, PreS1, and C were significantly enhanced and durable after boosted with RVJSS1 and RVJCS1. Our data support that HBV therapeutic vaccine candidates should incorporate the PreS1 and Core antigens. Abstract: Therapeutic vaccines represent a unique approach to hepatitis B virus (HBV) treatment and have the potential to induce long-term control of infection. This study explored the immune responses of rhesus macaques to novel vaccines comprising the S, PreS1, and Core antigens of the HBV that showed promise as prophylactic and therapeutic approaches in a mouse model. The tested vaccines included two DNA vaccines (pVRC-SS1, pVRC-CS1), an HBV particle subunit (HBSS1) vaccine and the recombinant vaccinia virus- (RVJ-) based vaccines (RVJSS1 and RVJCS1) in which SS1 containing S (1–223 aa) and PreS1 (21–47 aa), CS1 containing Core (1–144 aa) and PreS1 (1–42 aa). The humoral immunity and cell-mediated immunity (CMI) induced by vaccines comprising the S, PreS1, and Core antigens of HBV were investigated in a longitudinal study that continued up to 98 weeks after the first vaccination. In rhesus macaques, anti-PreS1 antibody was induced more rapidly than anti-S or anti-Core antibody after DNA vaccination. The antibody and cell-mediated immune responses against S, PreS1, and C were significantly enhanced in macaques boosted with RVJSS1 and RVJCS1, whereas the cell-mediated response to C was most robust and durable. The immune response to S, PreS1, and C was restored by HBSS1 boosting and detected in macaques until weeks 74 and 98 after the first vaccination. Additionally, robust neutralizing activity was detected at week 52. In conclusion, novel HBV vaccine candidates, especially those used for therapeutic applications should incorporate the PreS1 and Core antigens.